ANALISIS KETERAMPILAN GURU DALAM MENGAJAR SISWA INKLUSIF DI SDIT AL-BAYYINAH GARUT - Sunarti Cikal Putri, Aulia; Jenal Mutaqin, Ejen; Nabela, Indirawati; Maulida Syifaunnisa, Ajeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Inclusive education provides opportunities for students with special needs to learn alongside regular students within the same educational environment. The success of inclusive education is strongly influenced by teachers’ skills in planning, implementing, and evaluating learning, as well as in managing inclusive classrooms. This study aims to analyze teachers’ skills in teaching inclusive students at SDIT Al-Bayyinah Garut. The research employed a quantitative approach using a survey method. The population as well as the sample consisted of all teachers teaching at SDIT Al-Bayyinah Garut, totaling 24 teachers, selected using a saturated sampling technique. Data were collected through a closed-ended questionnaire based on a Likert scale covering aspects of lesson planning, learning implementation, learning evaluation, and inclusive classroom management. The data were analyzed using descriptive quantitative techniques to determine the level of teachers’ skills. The results indicate that teachers’ skills in teaching inclusive students fall into the good category. Teachers have been able to adjust lesson planning, apply varied instructional strategies, conduct flexible assessments, and create inclusive classroom environments. However, further improvement in teachers’ competencies is still required through continuous professional development, particularly in the use of instructional media and differentiated instruction. This study is expected to serve as an evaluation material and a reference for improving the quality of inclusive education implementation at the elementary school level.